Optimization of friction stir process parameters for fabrication of AA7075/TiO2 based surface composites. (26th November 2021) - Suganeswaran, K; Nithyavathy, N; Parameshwaran, R; Deepandurai, K; Muthukumar, P
Abstract: In this current investigation, Taguchi method is employed for the improvement of hardness and tensile strength of Friction Stir Processed (FSP) AA7075 with TiO2 reinforcement, which is potentially suited for manufacturing of components in automotive and aerospace applications. Controllable FSP process parameters like Rotational Speed (RS), Traverse Speed (TS), Tool Tilt Angle (TA) and number of passes (No. of pass) are taken into consideration. From Taguchi results, it is identified that No of pass as two, RS as 1400 rpm, TS as 28 mm min −1 and TA as 2° serves the most influencing statistical effect for yielding the hardness. Similarly for Ultimate Strength (UTS), it is identified that No of pass as one, RS as 1400 rpm, TS as 28 mm min −1 and TA of 3° are the influencing parameters. No defect like structure is apparent in the optimized specimens owing to the sufficient heat generation and stirring phenomenon. Besides, sufficient interaction between the plasticized AA7075 matrix and packed TiO2 particles in the SC eliminates the defect formation. Micrographs of the optimized specimens revealed that TiO2 particles are dispersed uniformly in AA7075 matrix with clear interface. Moreover, there is an increase in microhardness for optimized specimen compared to base specimen due to reduced grain size value and homogenous dispersion strengthening mechanism. Meanwhile, the load bearing capacity and work hardening action of TiO2 dispersoids enhances the UTS behavior of the optimized specimen.